2012
DOI: 10.1073/pnas.1210129109
|View full text |Cite
|
Sign up to set email alerts
|

cAMP response element modulator α controls IL2 and IL17A expression during CD4 lineage commitment and subset distribution in lupus

Abstract: Appropriate expression of IL-2 plays a central role during the priming and differentiation of T cells. A tight balance between IL-2 and the effector cytokine IL-17A is essential for immune homeostasis. Epigenetic mechanisms have been documented as a key component of cytokine regulation during lineage commitment. The molecular mechanisms that induce chromatin remodeling are less well understood. We investigated epigenetic regulators that mediate the diametric expression of IL-2 and IL-17A in naive, central memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
121
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 33 publications
(75 reference statements)
4
121
0
3
Order By: Relevance
“…We reported recently that CaMK4 can activate the transcription factor CREM-α (19,20), which mediates epigenetic remodeling of cytokine genes, including IL17 during the priming of CD4 + T cells from patients with SLE (35,53). Consistent with this, MRL/lpr.Camk4 -/-mice exhibited reduced CREM-α recruitment to the Il17 promoter, which led to decreased IL-17, arguing that the CaMK4-CREM-α…”
Section: Discussionsupporting
confidence: 60%
“…We reported recently that CaMK4 can activate the transcription factor CREM-α (19,20), which mediates epigenetic remodeling of cytokine genes, including IL17 during the priming of CD4 + T cells from patients with SLE (35,53). Consistent with this, MRL/lpr.Camk4 -/-mice exhibited reduced CREM-α recruitment to the Il17 promoter, which led to decreased IL-17, arguing that the CaMK4-CREM-α…”
Section: Discussionsupporting
confidence: 60%
“…Conflicting data exist regarding Stat5 in SLE (21,22). Although attenuated IL-2 expression in SLE T cells suggests reduced Stat5 activation (23)(24)(25), one study demonstrated increased Stat5 phosphorylation in SLE (22). In T cells from SLE patients and lupus-prone MRL/lpr mice, pStat3 is increased (19,26).…”
Section: Discussionmentioning
confidence: 99%
“…Expression plasmids for human DNMT3a have been described previously (24). Reporter constructs spanning the proximal 946 bp of the human IL10 promoter or a 630 bp-spanning fragment of the fourth intron with enhancer activity were PCR-amplified and cloned into luciferase vector pGL3-Basic (Promega).…”
mentioning
confidence: 99%
“…CREMα was found to bind to the IL17 promoter and to enhance its activity in vitro. In addition to the promoter, CREMα binds to additional sites across the IL17 locus but, unlike the IL2 locus, keeps the IL17 locus open because it fails to recruit HDAC1, G9α, and DNMT1 (67). Thus it appears that a single transcription factor, CREMα, accounts for both increased IL-17 production and decreased IL-2 production ( Figure 3).…”
Section: Limited Production Of Il-2mentioning
confidence: 99%
“…Effector CD4 + T cells are expanded in SLE patients and produce less IL-2 and more IL-17 than CD4 + T cells in healthy controls (67). It has been shown that CREMα limits the production of IL-2 and enhances the production of IL-17 in order to expand effector T cells in SLE patients (67). Thus, CREMα alone explains the aberrant numbers of potentially pathogenic T cell subsets.…”
Section: Increased Production Of Il-17mentioning
confidence: 99%